Analysis of conditional survival in primary hepatocellular carcinoma after narrow-margin hepatectomy: a large-sample, dual-centre, retrospective study. Issue 2 (February 2023) - Kong, Jie; Huang, Tingfeng; Zhang, Jianxi; Tang, Shichuan; Liu, Hongzhi; Liu, Jingfeng; Zeng, Yongyi
Abstract: Background: Overall survival (OS) reflects the constant hazard and survival probabilities calculated from the initial follow-up. Conditional survival (CS) dynamically estimates prognosis based on survival time after treatment. This study aimed to estimate CS in patients who had undergone narrow-margin hepatectomy for primary hepatocellular carcinoma. Methods: The clinical data of 1010 eligible patients between 2012 and 2017 were retrospectively analysed. The equation CS1=OS(x+1)/OS(x) was used to calculate the probability of an additional 1-year survival in patients who had survived for x years. Results: Tumour differentiation, microvascular invasion, and tumour emboli were independent risk factors for OS. Actuarial survival decreased from 91.53% at 1 year after hepatectomy to 48.92% at 4 years, whereas CS1 increased from 69.45% at 1 year to 94.62% at 4 years. The difference was more obvious in the tumour-emboli subgroup, with an OS of 26.38% at 5 years versus a CS1 of 88.91% at 4 years following narrow-margin hepatectomy (Δ62.53%). Conclusion: CS is potentially useful in providing a dynamic evaluation of survival, predicting prognosis more accurately than OS during follow-up, and formulating more appropriate treatment measures based on disease progression.